Role of microRNA/lncRNA Intertwined With the Wnt/β-Catenin Axis in Regulating the Pathogenesis of Triple-Negative Breast Cancer - Hu, Xue; Zhang, Qiang; Xing, Wanying; Wang, Wan (Frontiers in Pharmacology, 2022)
Malignant tumor formation is very high for breast cancer in women and a leading cause of death all over the globe. Among breast cancer subtypes, triple-negative breast cancer is rife in pre-menopausal women, most invasive, and prone to metastasis. Complex pathways are involved in the pathogenesis, advancement, and malignancy of this cancer, including the Wnt/β-catenin signaling pathway. This pathway is conserved among vertebrates and is necessary for sustaining cell homeostasis. It is regulated by several elements like transcription factors, enhancers, non-coding RNAs (lncRNAs, miRNAs), etc. In this mini-review, we discuss its modulation in triple-negative breast cancer, particularly the contribution of lncRNAs and miRNAs in its regulation and their possible entwining role with breast cancer pathogenesis, proliferation, migration, or malignancy.